VIOLATIONS IN THE COMMERCIALIZATION OF INFANT FORMULA FOR INFANTS IN COMMERCIAL ESTABLISHMENTS IN MACEIÓ, ALAGOAS - Romão, Dayse Andrade; de Freitas, Isabele Luzia Rodrigues Alves; de Novaes, Maria Clara Moreira Calheiros; do Nascimento, Giselle Medeiros; Rodrigues, Raphaela Farias; de Vasconcelos, Rafaela Andrade; Fragoso, Larissa Silveira de Mendonça; Reis, Mirella Medeiros (Seven Editora, 2026)
The Brazilian Standard for the Commercialization of Foods for Infants and Young Children, Nipples, Pacifiers, and Baby Bottles (NBCAL) aims to protect breastfeeding; however, violations have been identified that expose mothers and children to abusive marketing of products that compete with breastfeeding. Objective: To identify infractions of NBCAL in the commercialization of infant formula and follow-on infant formula in commercial establishments in the city of Maceió, Alagoas. Methodology: An observational and descriptive study was conducted through visits and verification of NBCAL violations in commercial establishments (supermarkets and pharmacies) located in different neighborhoods of Maceió, Alagoas. Results: Of the 126 establishments recorded in the study, 27 presented infractions, corresponding to 21.4% of the total. Among the establishments visited, 19.8% of pharmacies and 25.7% of supermarkets presented infractions, indicating that supermarkets showed a higher occurrence of improper commercial promotion. The predominant commercial strategy was price discounts, but special product displays and the combination of discounts with special displays were also observed. The two types of formula analyzed in the study presented similar rates of infractions. Conclusion: Noncompliance with regulations aimed at protecting breastfeeding was identified in some commercial establishments in Maceió, Alagoas, highlighting irregularities regarding NBCAL.